Tonicity induced changes in volume and refractive index of suspended cells quantified with digital holographic microscopy - Kemper, Björn; Klokkers, Jens; Przibilla, Sabine; Vollmer, Angelika; Ketelhut, Steffi; von Bally, Gert; Pavenstädt, Hermann-Joseph; Schlatter, Eberhard; Edemir, Bayram (Photonics Letters of Poland, 2012)
The analysis of changes of the volume and the intracellular solute concentrations of biological cells represents an important topic in cytometry. We present results from a comparative study in which the cell volume and the refractive index of living rat inner medullary collecting duct cells and human pancreatic tumor cells was determined in media with different tonicity by using quantitative digital holographic phase microscopy. The results show that the inverse cell volume correlates linearly with the integral cellular refractive index which is directly related to the concentration of intracellular solutes. Full Text: PDF References E. K. Hoffmann, O. H. Lambert, S. F. Pedersen, "Physiology of Cell Volume Regulation in Vertebrates", Physiol. Rev. 89, 193 (2009).CrossRef W. E. Crowe, J. Altamirano, L. Huerto, F. J. Alvarez-Leefmans, "Volume changes in single N1E-115 neuroblastoma cells measured with a fluorescent probe", Neuroscience 69, 283 (1995).CrossRef K. Maric, B. Wiesner, D. Lorenz, E. Klussmann, T. Betz, W. Rosenthal, "Cell Volume Kinetics of Adherent Epithelial Cells Measured by Laser Scanning Reflection Microscopy: Determination of Water Permeability Changes of Renal Principal Cells", Biophys. J. 80, 1783 (2001).CrossRef K. A. Poulsen, E. C. Andersen, C. F. Hansen, T. K. Klausen, C. Hougaard, I. H. Lambert, E. K. Hoffmann, "Deregulation of apoptotic volume decrease and ionic movements in multidrug-resistant tumor cells: role of chloride channels", Am. J. Physiol. Cell Physiol. 298, C14 (2010).CrossRef D. Carl, B. Kemper, G. Wernicke, G. von Bally, "Parameter-Optimized Digital Holographic Microscope for High-Resolution Living-Cell Analysis", Appl. Opt. 43, 6536 (2004).CrossRef P. Marquet, B. Rappaz, P. J. Magistretti, P. E. Cuche, Y. Emery, T. Colomb, C. Depeursinge, "Digital holographic microscopy: a noninvasive contrast imaging technique allowing quantitative visualization of living cells with subwavelength axial accuracy", Opt. Lett. 30, 468 (2005).CrossRef C. J. Mann, L. F. Yu, C. M. Lo, M. K. Kim, "High-resolution quantitative phase-contrast microscopy by digital holography", Opt. Express 13, 8693 (2005).CrossRef B. Kemper, D. Carl, J. Schnekenburger, I. Bredebusch, M. Schäfer, W. Domschke, G. von Bally, "Investigation of living pancreas tumor cells by digital holographic microscopy", J. Biomed. Opt. 11, 034005 (2006).CrossRef B. Rappaz, P. Marquet, E. Cuche, Y. Emery, C. Depeursinge, and P. J. Magistretti, "Measurement of the integral refractive index and dynamic cell morphometry of living cells with digital holographic microscopy", Opt. Express 13, 9361-9373 (2005).CrossRef B. Rappaz, F. Charrière, C. Depeursinge, P.J. Magistretti, P. Marquet, "Simultaneous cell morphometry and refractive index measurement with dual-wavelength digital holographic microscopy and dye-enhanced dispersion of perfusion medium", Opt. Lett. 33, 744 (2007).CrossRef B. Kemper, S. Kosmeier, P. Langehanenberg, G. von Bally, I. Bredebusch, W. Domschke, J. Schnekenburger, "ntegral refractive index determination of living suspension cells by multifocus digital holographic phase contrast microscopy", J. Biomed. Opt. 12, 054009 (2007).CrossRef M. Kemmler, M. Fratz, D. Giel, N. Saum, A. Brandenburg, C. Hoffman, "Noninvasive time-dependent cytometry monitoring by digital holography", J. Biomed. Opt., 12, 064002 (2007).CrossRef S. Kosmeier, B. Kemper, P. Langehanenberg, I. Bredebusch, J. Schnekenburger, A. Bauwens, G. von Bally, "Determination of the integral refractive index of cells in suspension by digital holographic phase contrast microscopy", Proc SPIE 6991 699110 (2008).CrossRef R. Barer, “Interference microscopy and mass determination,” Nature (London) 169, 366 (1952).CrossRef F. Charrière, N. Pavillon, T. Colomb, C. Depeursinge, T. J. Heger, E. A. D. Mitchell, P. Marquet, and B. Rappaz, "Living specimen tomography by digital holographic microscopy: morphometry of testate amoeba", Opt. Express 14, 7005-7013 (2006).CrossRef W. Choi, C. Fang-Yen, K. Badizadegan, S. Oh, N. Lue, R. R. Dasari, and M. S. Feld, "Tomographic phase microscopy", Nat. Meth. 4, 717-719 (2007).CrossRef M. Debailleul, V. Georges, B. Simon, R. Morin, O. Haeberlé, "High-resolution three-dimensional tomographic diffractive microscopy of transparent inorganic and biological samples", Opt. Lett. 34, 79-81. (2009).CrossRef T. Kozacki, R. Krajewski, M. Kujawińska, "Reconstruction of refractive-index distribution in off-axis digital holography optical diffraction tomographic system", Opt. Express, 17, 13758-13767 (2009).CrossRef J. Klokkers, P. Langehanenberg, B. Kemper, S. Kosmeier S, G. von Bally, C. Riethmuller, F. Wunder, A. Sindic, H. Pavenstädt, E. Schlatter, B. Edemir, "Atrial natriuretic peptide and nitric oxide signaling antagonizes vasopressin-mediated water permeability in inner medullary collecting duct cells", Am. J. Physiol. Renal. Physiol. 297, F693-F703 (2009).CrossRef B. Kemper, D. Carl, A. Höink, G. von Bally, I. Bredebusch, J. Schnekenburger, "Modular digital holographic microscopy system for marker free quantitative phase contrast imaging of living cells", Proc. SPIE 6191, 61910T (2006).CrossRef B. Kemper, A. Vollmer, C. Rommel, J. Schnekenburger, G. von Bally, "Simplified approach for quantitative digital holographic phase contrast imaging of living cells", J. Biomed. Opt. 16, 026014 (2011).CrossRef P. Langehanenberg, B. Kemper, D. Dirksen, G. von Bally, "Autofocusing in digital holographic phase contrast microscopy on pure phase objects for live cell imaging", Appl. Opt. 47, D176 (2008).CrossRef B. Rappaz, E. Canob, T. Colomb, J. Kühn, V. Simanis, C. Depeursinge, P. J. Magistretti, P. Marquet, "Noninvasive characterization of the fission yeast cell cycle by monitoring dry mass with digital holographic microscopy", J. Biomed. Opt. 14, 034049 (2009).CrossRef G. Popescu, Y. K. Park, N. Lue, C.-A. Best-Popescu, L. Deflores, R. R. Dasari, M. S. Feld, K. Badizadegan, "Optical imaging of cell mass and growth dynamics", Am. J. Physiol. Cell Physiol. 295, C538 (2008).CrossRef